STUDI KANDUNGAN LOGAM BERAT Pb DAN Cd DALAM SEDIMEN DI PERAIRAN PESISIR KECAMATAN GENUK SEMARANG - Veronika, Mahda; Suryono, Chrisna Adhi; Suryono, Suryono (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Heavy metals; lead (Pb) and cadmium (Cd) are commonly used in the industrial sectors, including the industryof batteries, pesticides, detergents, paints, and chemical factories. Heavy metals which get into the water can damage the ecosystems and organisms in it. The aim of this study is to determine the contents of heavy metals Pb and Cd in sediments at Genuk coast waters district, Semarang. This research was conducted on October 7, November12, and December112012 at Genuk Coast Water District, Semarang. The sampling was conducted in 8 stationpoints. The method used for the analysis of heavy metals wasAtomic Absorption Spectrophotometry (AAS), while the sediment fraction was analyzed using wet sieving method in Soil Mechanics Laboratory of the Faculty of Engineering, Diponegoro University. Based on the research result, the contents of heavy metals Pb was higher compared with Cd, i.e heavy metal Pb ranging from 13,99 ppm - 38,11 ppm and heavy metal Cdranging from 0,17 ppm – 0,25 ppm, while the percentage of sediment fraction in all research stations dominated by silt fraction. The resultof correlation test has showed a positive correlation between heavy metals Pb and Cd to the grain size and organic matter in the amount of 11.4% and 49.6%.